Human rights on trial : a genealogy of the critique of human rights - Lacroix, Justine (Human rights in history, 2016)
"Fragmented social relations, the twin demise of authority and tradition, the breakdown of behavioural norms and constraints: all these are the outcome, according to their critics, of the uses and abuses of human rights in contemporary democratic societies. We are, they say, seeing the perverse effects of a 'religion of human rights' to which Europe has rashly devoted its heart and mind; and the supposed burgeoning of rights, which goes hand in hand with an unchecked rise of expectations, is catapulting Western democracies into an age of never-ending demands. This emerged clearly in France in Spring 2013 during the demonstrations against equal marriage ('mariage pour tous') whose opponents deplored the excesses of a movement-driven left striving for an unbounded extension of rights - from the right to same-sex marriage to the enfranchisement of non-nationals or the right of same-sex couples to adopt"--